STUDY OF THE OZONE CONTROL PROCESS USING ELECTRONIC SENSORS - Marxuly, Sunggat; Abdykadyrov, Askar; Chezhimbayeva, Katipa; Smailov, Nurzhigit (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
In research work the problem of studying the process of ozone control with the help of electronic sensors is considered. In research work, special sensors were used, which are formed around coronary electrodes in the ozonator and to monitor the concentration of ozone in the room. This is because ozone is known to adversely affect human health if its maximum permissible air concentration exceeds 0.16 mg/m3. A small system of ozonators was developed in a special laboratory, theoretical and experimental tests were carried out. In practice, the obtained data and the electric diagram of the ozonator (on the ARDUINO platform) were collected. "Prana Air" sensors and current sensors were used to accurately determine the ozone (O3) concentration around the ozone nozzle to measure the current at the electrodes.